Experiment on Power Quality of PV-grid System at FKEE UMP - Muhammad Ikram, Mohd Rashid; Suliana, Abd Ghani; Nur Yasmin, Amran; Akorede, Mudathir Funsho (2012)
This paper presents experiments of PV-grid system operation for a day light consisting of Photovoltaic (PV) – Inverter system as the renewable source connected to a network of induction motor as the load. A small-scale laboratory consists of Photovoltaic, Inverter, and loads system was setup. One power supplies from PV and grid were connected to single phase induction motors. In the experiment, both energy supplies from the grid and photovoltaic system were connected to the loads. Measurements have been done at both side of power transformer to analyze power quality in the system.